Vertical Integration in the Pediatrics Clerkship: A Case Study - Julianne M. Hall; Rahul Anand; Lynn E. Copes; Kelly Moran-Crusio; J. Nathan Davis; Maya Doyle; Christine Maffeo; Eitan S. Kilchevsky (MDPI AG, 2023)
Since the end of the twentieth century, medical educators continue to review and call for changes that will improve how medical students apply their knowledge of basic sciences to the clinical management of their patients. The traditional 2 + 2 curriculum, where basic sciences are taught during the first two years and were followed by clinical clerkships, was challenged with calls to move towards a Z-shaped integrated curriculum, a model which presents bio-medical sciences and clinical cases in parallel or in connection with one another. Faculty at the Frank H. Netter MD School of Medicine developed a vertical integration didactic session that presented an eight-year-old child with an acute asthmatic episode. After a brief introduction, clinical and pre-clinical faculty who teach in Years 1-3 and social work faculty met with medical students placed in small groups to discuss their pertinent field; faculty members rotated among the groups. At the end of the session, the students provided feedback and comments for the continuous quality improvement of the session. The session has been taught four times thus far. A majority of the students expressed satisfaction with the opportunity to review basic science concepts during the clerkship and apply these concepts to develop clinical management skills. Students were also excited to discuss social determinants and the effects of a pediatric chronic illness on the whole family. Combining a review of basic and social science concepts with clinical management, with faculty from pre-clinical and clinical years, was enjoyed by our students, who felt this educational approach expanded their ability to better manage clinical problems. While our case is in pediatrics, we believe the method can be applied to other specialties.